Analysis of the Effect of Display and Promotion on Purchase Decisions at Surya Toserba Cirebon - Ruhida Taufik (Universitas KH. Abdul Chalim Mojokerto, 2026)
Tight competition in the modern retail industry encourages companies to implement appropriate marketing strategies, particularly through product display arrangements and sales promotions. This study aims to analyze the influence of displays and promotions on consumer purchasing decisions at Surya Toserba Cirebon. The method used is quantitative with a descriptive and associative approach, using a questionnaire instrument on 101 respondents. Validity and reliability tests show that all indicators in the research variables are valid and reliable with a Cronbach's Alpha value > 0.9. The results of multiple regression analysis indicate that displays and promotions have a positive and significant effect on purchasing decisions, both partially and simultaneously. The coefficient of determination (R²) value of 0.562 indicates that both variables are able to explain 56.2% of the variation in consumer purchasing decisions, while the remainder is influenced by other factors outside the research model. Promotions are proven to have a more dominant influence than displays, indicating that consumers are more responsive to promotional incentives such as discounts, vouchers, and bundling. These findings imply that retail management needs to combine attractive display strategies with varied promotions to increase sales effectiveness.